2021
DOI: 10.1088/1755-1315/713/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Application of pumping and rice planting patterns to improve the productivity of fresh water swampy rice fields in South Sumatra, Indonesia

Abstract: Productivity of the fresh water rice fields is currently relatively low due to various factors such as cropping patterns and water factors. This study aimed to compare four cropping patterns in cultivation of swampy fresh water rice. The four cropping patterns consisted of the cropping patterns of Farmer Entrepreneurs, Conventional Farmers, Fostered Farmers of Jajar Legowo Super, and Fostered Farmers of Tegel Diairi. The study used descriptive method by collecting primary data presented in tabular forms. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Furthermore [16] reported that this approach is convenient in terms of fertilization, weeding, and pest and disease control. Finally, this system has the potential to increase rice productivity by 10-15% [17]. The success of the jajar legowo planting system needs to be supported by the use of modern tools such as jajar legowo 4:1 seeders, jajar legowo dipsticks 2:1 and transplanters (seedling planting tools) in order to shorten planting time and the workforce [15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore [16] reported that this approach is convenient in terms of fertilization, weeding, and pest and disease control. Finally, this system has the potential to increase rice productivity by 10-15% [17]. The success of the jajar legowo planting system needs to be supported by the use of modern tools such as jajar legowo 4:1 seeders, jajar legowo dipsticks 2:1 and transplanters (seedling planting tools) in order to shorten planting time and the workforce [15].…”
Section: Introductionmentioning
confidence: 99%